Two-Fluid Cosmological Model of Bianchi Type-V with Negative Constant Deceleration Parameter - Singh M.K.; Verma M.K.; Ram S. (My University, 2025)
This paper deals with a two-fluid Bianchi type-V anisotropic cosmological model with negative constant deceleration parameter. Exact solution of Einstein's field equations for interacting matter and radiation field is presented which represents an expanding shearing and nonrotating cosmological model of the universe. This model describes the accelerated phase of the expanding universe. The physical and kinematical behaviors of the model are discussed. © 2012 Springer Science+Business Media, LLC.